2021
DOI: 10.4097/kja.21234
|View full text |Cite
|
Sign up to set email alerts
|

Video laryngoscopy vs. direct laryngoscopy for nasotracheal intubation in oromaxillofacial surgery: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background: Nasotracheal intubation (NTI) is commonly performed in oromaxillofacial surgeries. We did this metanalysis to ascertain whether use of video laryngoscopy (VL) provided better NTI characteristics as compared to direct laryngoscopy (DL) in patients undergoing oromaxillofacial surgeries.Methods: We performed a systematic search to identify randomized controlled trials comparing VL with DL for NTI in adults undergoing elective oromaxillofacial surgery. The primary outcome was time to intubation. Second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Importantly, all the TSAs confirmed the robustness of the findings of Gupta et al [1] as the Z-curve of effect crossed the adjusted significance thresholds in all analyses.…”
Section: Dear Editorsupporting
confidence: 76%
See 2 more Smart Citations
“…Importantly, all the TSAs confirmed the robustness of the findings of Gupta et al [1] as the Z-curve of effect crossed the adjusted significance thresholds in all analyses.…”
Section: Dear Editorsupporting
confidence: 76%
“…We congratulate Gupta et al [1] for conducting a very interesting meta-analysis on the comparative characteristics of video laryngoscope (VL) compared to direct laryngoscope (DL) for nasotracheal intubation (NTI) in oro-maxillofacial surgeries.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies indicate no overall difference in the success rate of intubation between VL and DL during NTI [ 13 45 ], a meta-analysis by Jiang et al reported that VL increases the first attempt success rate (relative risk (RR), 1.09; 95% CI, 1.00–1.17; n = 930; P = 0.04), especially in cases of difficult airways [ 45 ]. Park et al reported higher success rates on the first attempt in groups using VL than in those using DL (93.8% vs. 74.8%, P < 0.001) [ 56 ].…”
Section: Nti Experience and Success Rate Under Vlmentioning
confidence: 99%
“…In the existing literature on the application of VL for NTI, the specific advantages in oral and maxillofacial surgical contexts have not been as extensively documented as those in other areas of surgical practice [ 12 13 ].…”
Section: Introductionmentioning
confidence: 99%